Analisis Ekonomika Kebahagiaan: Pengaruh Pendapatan Dan Kesetaraan Terhadap Tingkat Kepuasan Hidup - Salsabila, Nanda Della; Maharani, Anisa; Hasanah, Miftahul; Puspita, Melya; Sanjaya, Vicki F (-, 2025)
This study aims to analyze the effect of income per capita and economic equality on the level of happiness of the Indonesian society. The research method used is a quantitative approach with multiple linear regression to examine the relationship between the variables of income, economic equality (Gini Index), and societal happiness. The data used in this study was obtained from the Central Bureau of Statistics (BPS) and the World Happiness Report 2020-2024. The research results show that income per capita positively influences happiness, although its impact decreases once basic needs are met. In addition, economic equality also has a significant positive effect on happiness, indicating that a more equal distribution of income can increase social happiness. The conclusion of this study is that policies aimed at increasing income per capita and supporting more equitable wealth redistribution can contribute to improving the happiness of the Indonesian society.